OBJECTION TO PROCESSING PERSONAL DATA AS AN EXPRESSION OF THE RIGHT TO PRIVACY - Morawska, Katarzyna (Człowiek w cyberprzestrzeni, 2020)
Steady technological development stems from ever larger body of data being processed; as a result profiles of service users – data subject may be created. In times when we more or less consciously decide to share our private sphere, the right to privacy must be specially protected. This right is inextricably linked with the need to exercise effective control over the transferred data, and hence awareness must be built on the purposes and method of personal data’s possible processing by the controllers. The publication argues that the right to object to data processing expresses the right to privacy viewed as the right to control the processes of personal data processing and to exercise real control over how data controllers may use personal data. However, neither the rights, including the right to object, nor other institutions protecting privacy under GDPR will be properly exercised and applied unless they strictly link the protection mechanisms - this is a novelty implemented by GDPR to make the regulatory rights and obligations more effective. The publication will also consider the administrative sanctions that the supervisory authority may impose on personal data controllers or processors for non-compliance with the rules on data subjects' rights.